2021
DOI: 10.1016/j.jaccao.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Wild-Type Transthyretin Amyloid Cardiomyopathy in the Transthyretin Amyloidosis Outcomes Survey

Abstract: Background Transthyretin amyloid cardiomyopathy results from the accumulation of wild-type (ATTRwt) or variant (ATTRv) transthyretin amyloid fibrils in the myocardium. THAOS (Transthyretin Amyloidosis Outcomes Survey) is a global, longitudinal, observational survey of patients with ATTRv and ATTRwt amyloidosis and asymptomatic patients with transthyretin mutations. Objectives This study explored temporal trends in ATTRwt amyloidosis diagnoses using data from THAOS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“… 6 An analysis from the Transthyretin Amyloidosis Outcomes Survey (THAOS) found that despite the rising use of scintigraphy in diagnosis, half of ATTR wild-type CA patients experienced diagnostic delay >4.7 years. 24 The observed improvement in diagnostic delay in our study, may partly be explained by the new drug treatment in ATTR-CA launched in 2018, leading to an increase in scientific papers, presentations on (inter)national congresses, revision of diagnostic algorithms and the help of pharmaceutical industry with flyers and symposia. 23 , 25 As CA in general, including AL-CA, was in the spotlights, this probably also contributed to an improvement in the diagnostic delay.…”
Section: Discussionmentioning
confidence: 61%
“… 6 An analysis from the Transthyretin Amyloidosis Outcomes Survey (THAOS) found that despite the rising use of scintigraphy in diagnosis, half of ATTR wild-type CA patients experienced diagnostic delay >4.7 years. 24 The observed improvement in diagnostic delay in our study, may partly be explained by the new drug treatment in ATTR-CA launched in 2018, leading to an increase in scientific papers, presentations on (inter)national congresses, revision of diagnostic algorithms and the help of pharmaceutical industry with flyers and symposia. 23 , 25 As CA in general, including AL-CA, was in the spotlights, this probably also contributed to an improvement in the diagnostic delay.…”
Section: Discussionmentioning
confidence: 61%
“…Diagnosing ATTRwt amyloidosis can be particularly challenging because cardiac symptoms are often consistent with more common types of heart failure, and historically a diagnosis has been obtained through endomyocardial biopsy, an invasive and expensive technique [ 6 , 25 ]. It is expected that increased use of bone scintigraphy, a minimally invasive and less expensive diagnostic tool, would decrease the time to diagnosis among these patients [ 3 , 6 ], although this effect has not yet been reflected in THAOS [ 26 ]. Patients with early-onset Val30Met disease had the shortest time to diagnosis, but there was still an average 2 years from symptom onset to obtain a diagnosis despite most of these patients being from countries with endemic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should consider the early identification of affected individuals with widely available non-invasive diagnostic techniques. Real-world observations suggest that the increased awareness and availability of minimally invasive diagnostic tools, such as bone scintigraphy in the absence of a monoclonal protein, have contributed to a greater proportion of patients being diagnosed in NYHA class I or II over time, highlighting a shift to earlier diagnosis and the growing importance of these patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of tafamidis on the frequency and duration of CV-related hospitalizations was numerically more favorable in patients with wild-type ATTR-CM. Considering that a recent publication reported that wild-type patients made up the vast majority of diagnoses over the past decade, particularly in the USA, the results of our study could be considered a conservative estimate of the reduction in hospitalization burden for the real-world ATTR-CM population [ 16 ]. Likewise, there was a similar effect in frequency and duration of CV-related hospitalizations in both tafamidis doses (80 mg and 20 mg).…”
Section: Discussionmentioning
confidence: 99%